2021
DOI: 10.1097/ede.0000000000001393
|View full text |Cite
|
Sign up to set email alerts
|

Weight Change and the Onset of Cardiovascular Diseases: Emulating Trials Using Electronic Health Records

Abstract: Background: Cross-sectional measures of body mass index (BMI) are associated with cardiovascular disease (CVD) incidence, but less is known about whether weight change affects the risk of CVD. Methods: We estimated the effect of 2-y weight change interventions on 7-y risk of CVD (CVD death, myocardial infarction, stroke, hospitalization from coronary heart disease, and heart failure) by emulating hypothetical interventions using electronic health records. We identified 138,567 individuals with 45-69 years of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 30 publications
1
30
0
3
Order By: Relevance
“…25 Additionally, the increasing trends in BMI are combined with an increasing prevalence of diabetes in young adults. 10 From the perspective of both obesity prevention and health in young adults, it is important to address the challenge that, with the exception of pregnancy complications, most of the adverse health consequences of obesity and weight gain (including severe COVID-19, cardiovascular disease, and type 2 diabetes) 26 occur decades later, in middle-age and older age. Finally, repeated lockdowns during the COVID-19 pandemic have profoundly reduced the amount of physical activity and energy expenditure in young adults, which has had adverse effects on weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…25 Additionally, the increasing trends in BMI are combined with an increasing prevalence of diabetes in young adults. 10 From the perspective of both obesity prevention and health in young adults, it is important to address the challenge that, with the exception of pregnancy complications, most of the adverse health consequences of obesity and weight gain (including severe COVID-19, cardiovascular disease, and type 2 diabetes) 26 occur decades later, in middle-age and older age. Finally, repeated lockdowns during the COVID-19 pandemic have profoundly reduced the amount of physical activity and energy expenditure in young adults, which has had adverse effects on weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…The dyspnoeic effects on individuals could potentially promote a more sedentary lifestyle, in turn increasing the cardiovascular risk of such a population. Weight gain and a decreased level of fitness can arise as a subsequent consequence of such lifestyles, thus highlighting the importance of understanding the relationship between dyspnoea and the use of N95 respirators [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…Stevens et al [ 11 ] found that earlier weight gain over a long interval was associated with increased risks of CHD and ischemic stroke, whereas later, weight loss over a shorter interval was associated with increased immediate CHD and stroke risk, when compared with weight maintenance. Katsoulis et al [ 22 ] estimated the effect of 2-year weight change interventions on 7-year risk of CVD, and results found that weight maintenance group had a lower CVD risk compared with the weight gain and the weight-loss group among normal-weight individuals. While, among individuals with overweight, the weight loss and weight gain groups had a slightly higher CVD risk compared with weight maintenance.…”
Section: Discussionmentioning
confidence: 99%